2011
DOI: 10.4141/cjas10063
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Near infrared reflectance spectroscopy accurately predicts the digestible energy content of barley for pigs

Abstract: Zijlstra, R. T., Swift, M. L., Wang, L. F., Scott, T. A. and Edney, M. J. 2011. Short Communication:Near infrared reflectance spectroscopy accurately predicts the digestible energy content of barley for pigs. Can. J. Anim. Sci. 91: 301–304. Density, chicken apparent metabolizable energy (AME), and near infrared reflectance spectroscopy (NIRS) were tested to predict the widely varying swine digestible energy (DE) content of barley. The DE content of 39 barley samples ranged from 2686 to 3163 kcal kg−1 (90% DM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…To our knowledge, there is no existing reference on faecal NIRS prediction of nutritional value in the pig, although some references exist on prediction with feed spectra (e.g. Zijlstra et al, 2011). The relatively low variation in digestibility in our data set makes it quite difficult to obtain good calibration models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is no existing reference on faecal NIRS prediction of nutritional value in the pig, although some references exist on prediction with feed spectra (e.g. Zijlstra et al, 2011). The relatively low variation in digestibility in our data set makes it quite difficult to obtain good calibration models.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be performed by NIRS with calibration equations predicting nutritional value from feed spectrum within a specific family of ingredients (e.g. Zijlstra et al, 2011). The NIRS is based on the absorption of (IR) light by the chemical bonds of samples.…”
Section: Introductionmentioning
confidence: 99%
“…The parallel relationships among these corn sources imply that factors limiting energy availability were similar across species; this suggests that DE values for swine of these corn sources can be predicted from AME N or NIT-AME N measurements. In contrast, Zijlstra et al (2011) were unable to model swine DE (R 2 = 0.03) based on the AME of barley measured in young broilers and growing pigs and concluded that broiler AME could not be used to predict swine DE. This likely was due to a difference among species in response to additional fiber or in their capacity to digest NDF components.…”
Section: Digestible Energy Prediction Based On Nitrogen-corrected Appmentioning
confidence: 98%
“…Existing prediction models developed from indirect predictions may be imprecise for individual feed ingredients as the models were derived using mixed diets (Morgan et al, 1987;Noblet and Perez, 1993). Previous studies (Campbell et al, 1983;Sibbald et al, 1983;Smith et al, 1987Smith et al, , 1988 have demonstrated that data from rats and roosters can be used to predict DE and apparent ME (AME) for swine across a variety of feedstuffs and mixed diets, but cross-species comparisons with a single feedstuff are limited (Charmley and Greenhalgh, 1987;Zijlstra et al, 2011). Predicting DE values for swine from measurements with broilers or roosters could reduce both grain quantity and assay time required.…”
Section: Introductionmentioning
confidence: 99%
“…Chez le porc, quelques travaux ont été publiés sur la prédiction de la valeur énergétique (Energie digestible, ED) par SPIR (Zijstra et al, 2011 ;Li et al, 2016). Cependant ces études ont été réalisées sur des jeux de données assez restreint et la méthode ne peut actuellement pas être considérée comme validée (Święch, 2017).…”
Section: Prédiction De La Valeur éNergétiqueunclassified